Integrating Gotong Royong and Ukhuwah Islamiyah: Establishing a Reciprocity Ecosystem to Foster Tolerance for Children with Special Needs - Supriyanti, Iin; Nabila, Hanifatun; Murtadlo, Nashihul Faiq Dhofir (Proceeding International Conference on Religion, Science and Education, 2026)
This research aims to integrate the cultural values of Gotong Royong and the theological concept of Ukhuwah Islamiyah in forming a reciprocity ecosystem that supports tolerance for Children with Special Needs (ABK) in the dormitory environment. Gotong Royong as an Indonesian social tradition emphasizes selfless cooperation, while Ukhuwah Islamiyah emphasizes faith-based brotherhood. Both are seen as important foundations in building a harmonious inclusive society. The focus of the research is the Babanul Amanah Foundation in Madiun, a dormitory that accommodates 39 children with various disabilities (blind, deaf, deaf, and ADHD) with limited companions. The research method uses a qualitative approach of ethnographic case studies through participatory observation, semi-structured interviews, and documentation. Data analysis is carried out through reduction, presentation, and verification by triangulating sources, techniques, and time to ensure validity. The results of the study show that the limited number of companions actually gives birth to solidarity and independence among crew members. Daily picketing practices, the division of tasks according to ability, and the habit of helping each other in worship and self-care activities are a tangible manifestation of internalizing the value of mutual cooperation and ukhuwah. Tolerance in the dormitory develops to the stage of pure empathy, where children accept differences and fill in the shortcomings of others with real actions without discrimination. The research discussion emphasized that the merger of Gotong Royong and Ukhuwah Islamiyah forms a model of a functional reciprocity ecosystem. This model not only reduces the internal stigma against crew members, but also fosters organic solidarity according to the perspectives of social functionalism of Durkheim and Parsons. The implications of the study show that a dormitory system based on the value of togetherness can be an effective social and inclusive education strategy in building tolerance, empathy, and acceptance of ABK. Thus, the integration of cultural and religious values is able to create an educational environment that is fair, sustainable, and oriented towards the development of the potential of each individual.